Comparison of critical thinking skills of grade 4 students in pancasila education lessons at SDN Sepang between problem based learning models and conventional methods - Aryanti, Eka Tiara; Supriatna, Encep (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
According to the results of PISA 2018 students, Indonesian students are in the low performance quadrant with high quality and show low critical thinking skills, especially in solving complex thinking problems. This situation highlights the need to improve the standard of education, particularly in primary schools. A number of studies have been conducted to overcome this problem, one of the strategies that has succeeded using the Problem Based Learning (PBL) model. This model encourages the development of critical thinking skills in students by solving problems that require in-depth analysis. The purpose of this study is to examine how the PBL model affects student performance in learning Pancasila education at SDN Sepang. The research method used was a quasi experiment with the population of all 4th grade students of SDN Sepang,where class IVA was the experimental class while class IVB was the control class. The data analysis technique uses a description test instrument through pretest and posttest. The results of the data analysis showed that the Problem Based Learning model applied in the experimental class was larger than the control class that used conventional methods. The critical thinking ability of students who used the PBL model obtained an average score of 78.00, while students who used conventional methods obtained an average of 68.41. This research shows that the PBL model can improve students’ critical thinking skills and benefit the learning process in elementary schools.